THE ADOPTION OF ELECTRONIC COMMERCE (E-COMMERCE) BY SMALL MEDIUM ENTERPRISE IN MAKING FINANCING DECISION - Suhaimi, Shadia Binti; Hashim, Haniza Binti; Raaji, Rahja Raajeswary; Ganesan, Jaya (PEOPLE: International Journal of Social Sciences, 2015)
Electronic commerce (e-commerce) is a very important strategic tool that fascinates many companies to turn their traditional business strategy into e-commerce technology. Nowadays, the use of e-commerce is growing among business organizations throughout the world. It’s not only limited to large companies, but also includes Small and Medium Enterprises (SMEs). The reason why businesses are moving towards of using e-commerce systems because this technology is very cost effective and can make day-today business operations are much more easier. However, some of the SMEs are still underexploited on the potential of e-commerce. Therefore, this paper will be focusing on the discussion about the adoption of E-commerce in small and medium sized business based on the financial decision-making. Journal, case study and articles have been used to support all the discussion and argument on the research problem.